Diseño y desarrollo del manual de procedimientos y buenas prácticas para la gestión de los talleres de mantenimiento del gobierno autónomo descentralizado del cantón Quijos - Campaña Otero, Camila Juliana (2015)
This Grade project conducted under the auspices of the Decentralized Autonomous Municipal Government of Quijos, has been developed within the scope defined by its authorities and focused on the maintenance workshops of the institution that under a previous analysis was defined as critical and could be improved .on which we have developed the chapters of this project. It based on the initial study of reality together with the staff of maintenance workshop was held, applying improvement tools defined by selecting the most useful for this area. Making a report on the operation of the process and running a FMEA analysis (Failure Mode and Effects) activities and opportunities where we could implement such tools are determined. According to the objectives set for this project resulting from the analysis with the sponsor decided to perform a control plan that contains the critical activities that were identified in the FMEA (Failure Mode and Effects) and ensure its operation through a series of tools and controls that will be reflected in the “MANUAL OF PROCEDURES AND BEST PRACTICES FOR THE MAINTENANCE MANAGEMENT WORKSHOP OF DECENTRALIZED AND SELF-GOVERNMENT OF QUIJOS”, which is set to deliver the document to the sponsor as standard use when deciding to apply. We concluded at the end of these control tools implemented disciplined ensure the best use of resources and the fulfillment of the functions of the maintenance shop.